PENINGKATAN PENGETAHUAN KONSEPTUAL SISWA DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING - IKA TRISNI SIMANGUNSONG; Dede Parsaoran Damanik; Jelita Panjaitan (Jurnal Darma Agung, 2020)
This study aims at determining the students' conceptual knowledge improvement in using the Problem Based Learning model. This study is quasi-experimental with the design of the pretest-posttest group, in which the population is the tenth grade students of Yapim Taruna High School. The instrument in this study is in the form of essays that had been tested for validity, reliability, level of difficulty and different power. The results of this study show an improvement of students' conceptual knowledge in the experimental class by using a model of problem based learning is better than the control class